A brief history of the generic classification of the Trochilini (Aves: Trochilidae): the chaos of the past and problems to be resolved - Stiles, F. Gary; Piacentini, Vitor De Q.; Remsen, Jr., J. V. (Zootaxa, 2017)
The generic classification of the Trochilidae is unusually complicated because early authors, faced with a deluge of specimens with little or no data, often based species and genus names on superficial plumage characters derived from figured plates of varying artistic quality and reproduction. Working independently and with little knowledge of species distributions and with the fixation of type species for genera inconsistent or ignored, these authors produced a bewildering array of generic synonyms. The generic nomenclature of the largest and most recently derived clade of hummingbirds, the tribe Trochilini or “emeralds”, presents an unusually tangled web. Here we review the history of hummingbird generic nomenclature from Linnaeus to the present, giving detailed attention to two generic names that epitomize this confusion: Amazilia (the variety of spellings, supposed type species and circumscriptions makes for an especially complicated tangle) and Leucippus (for which nearly every successive author has advocated a different circumscription). Through application of the International Code for Zoological Nomenclature, this review lays the foundation for a revision of the generic nomenclature of the emeralds to bring it into conformity with recent genetic studies elucidating the phylogeny of this clade.